Ecolinguistic study of the IKN discourse in global and national news media - Kurniawan Agus Fiqih Budiman; Ribut Wahyudi (JOALL (Journal of Applied Linguistics and Literature), 2026)
This study aims to examine how news outlets construct discourse about Indonesia’s new capital (IKN) in North Penajam Paser, East Kalimantan. The researchers employed Stibbe's (2015) ecolinguistic framework. The problem lies in the contrasting views between stakeholders and indigenous communities of East Kalimantan toward such development. Therefore, this study bridges the gap by discovering how both parties defend their stances: “Is IKN an ideal project or not?” This study adopted a textual analysis technique, with relevant data collected from Al Jazeera, CNN, and Tempo.co between January 18, 2022, and March 19, 2025. The researchers used a note-taking technique and mapped each text onto Stibbe's (2015) ecolinguistic stories of ideology, framing, evaluation, and identity. Furthermore, the researchers classified each text based on modal verbs such as “should,” “must,” and “will,” adjectives such as “good” or “bad,” and phrasal nouns such as “environmental activists.” The results show that the story of evaluation appears more frequently, accentuating people’s negative responses, evidenced by terms such as “haunting,” “miserable lives,” and “shrinking.” The researchers affirm that the news media tend to report narratives of a conflict between neoliberal agendas (the government) and ecological sustainability (indigenous tribes of East Kalimantan).